2018
DOI: 10.1111/ijcs.12470
|View full text |Cite
|
Sign up to set email alerts
|

Awe, spirituality and conspicuous consumer behavior

Abstract: Awe represents a self‐transcendent, sacred experience that is closely related to spirituality. In this study, we suggest that spirituality buffers the effect of awe on materialistic consumption. Across three studies (N = 896), we test the hypothesis that awe can prompt participants’ spirituality, which in turn decreases the inclination of conspicuous consumption. In a survey, dispositional awe is found to be negatively related to the inclination of conspicuous consumption (Study 1). In follow‐up experiments, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 61 publications
0
22
1
1
Order By: Relevance
“…Perception of fractal patterns is also commonly associated with the visual imagery elicited by psychedelics ( Klüver, 1966 ; Varley et al, 2020 ). Awe is deeply tied to feelings of spirituality ( Hu et al, 2018 ; Kearns and Tyler, 2020 ; Preston and Shin, 2017 ; Van Cappellen and Saroglou, 2012 ), and spirituality and nature relatedness appear to be strongly linked ( de Jager Meezenbroek et al, 2012 ; Dömötör et al, 2017 ; Saraglou et al, 2008 ; Trigwell et al, 2014 ). Spirituality can act as a mediator between nature relatedness and contact with nature and psychological well-being ( Kamitsis and Francis, 2013 ; Knepple Carney and Patrick, 2016 ; Trigwell et al, 2014 ).…”
Section: Potential Beneficial Synergy Of Psychedelics and Nature Contmentioning
confidence: 99%
“…Perception of fractal patterns is also commonly associated with the visual imagery elicited by psychedelics ( Klüver, 1966 ; Varley et al, 2020 ). Awe is deeply tied to feelings of spirituality ( Hu et al, 2018 ; Kearns and Tyler, 2020 ; Preston and Shin, 2017 ; Van Cappellen and Saroglou, 2012 ), and spirituality and nature relatedness appear to be strongly linked ( de Jager Meezenbroek et al, 2012 ; Dömötör et al, 2017 ; Saraglou et al, 2008 ; Trigwell et al, 2014 ). Spirituality can act as a mediator between nature relatedness and contact with nature and psychological well-being ( Kamitsis and Francis, 2013 ; Knepple Carney and Patrick, 2016 ; Trigwell et al, 2014 ).…”
Section: Potential Beneficial Synergy Of Psychedelics and Nature Contmentioning
confidence: 99%
“…Positive emotions, in particular, are roundly shown to have a favourable effect on consumer behaviour and to have an important role in repeat purchase behaviour (Donovan et al, 1994;Yalch & Spangenberg, 2000). We focus first on the positive emotion of pride because it has been shown to influence product choice (Hampson & McGoldrick, 2017;Hu et al, 2018;Huang et al, 2014;Ladhari & Tchetgna, 2017) and should be influenced based on a consumer's level of religiosity, given many statements related to pride in religious scripture (Schmidt et al, 2014).…”
Section: Pride and Extrinsic Religiositymentioning
confidence: 99%
“…Intrinsic religiosity is oftentimes associated with reduced materialism (Chowdhury, 2018;Minton et al, 2016), meaning that one potential area of conflict is with the materialistic desires that holiday advertising appeals to. In fact, research has both identified 'limiting exposure to advertising' as a tactic used to support a consumer lifestyle of voluntary simplicity (Huneke, 2005) and that the induction of awe, a self-transcendent scared experience closely related to spirituality, decreases conspicuous consumption (Hu et al, 2018). Moreover, most religions seek to moderate materialistic desires and encourage believers to transcend these wants by focusing on their religious beliefs and practices as well as other attitudes/behaviours that are more important than purely the acquisition of physical belongings (Casabayó et al, 2020;Minton et al, 2016;Raggiotto et al, 2018;Schmidt et al, 2014).…”
Section: Guilt and Intrinsic Religiositymentioning
confidence: 99%
“…It is noted that awe exerts significant effects on individuals' judgment and decision-making (e.g. Hu et al , 2018; Rudd et al , 2018; Yang and Hu, 2021). However, most of the extant research on awe is conducted in general social contexts, with very few studies in business settings.…”
Section: Introductionmentioning
confidence: 99%